Afro-American Women Discrimination on Hidden Figures : A Critical Discourse Analysis - Listiana Ikawati (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
This study investigates the discrimination against three Afro-American women in Hidden Figures. Critical Discourse Analysis proposed by Fairclough (2012) was used in this study to deconstruct the discrimination and provide solutions to tackle the problem. The CDA was supported by the analysis on language through Systemic Functional Grammar by Halliday (2004) and the analysis on body language by Jäger and Maier (2009). The result shows that the discrimination in the movie can be differentiated into discrimination based on the level and the cause. The discrimination based on the level includes the individual, institutional and structural discrimination. Based on the cause, discrimination based on race (racism) and dis- crimination based on gender (sexism) are illustrated in the movie. The racism is developed from racist ideology, while the sexism is caused by sexist ideology. Finally, the ideologies are represented through language and body language.